A new earthworm species of the genus Rhinodrilus (Rhinodrilidae, Clitellata) and new records of earthworms species from the Amazon-Cerrado-Caatinga transition in the State of Maranhão, Brazil - Sousa, Sandriel Costa; de Sousa, Anny Mykaelly; Hernández-García, Luis Manuel; Gualter, Regia Maria Reis; Rousseau, Guillaume Xavier (Zootaxa, 2020)
We describe a new species of the genus Rhinodrilus from the transition between the Amazon, Cerrado and Caatinga biomes in the State of Maranhão, Brazil. The region is currently being converted to large-scale agriculture, which may cause severe losses in the local fauna and flora diversity yet very poorly studied. Rhinodrilus antonioi sp. nov. has irregular setae in the posterior region of the body, spermathecae without diverticula, tubercula pubertatis in the form of band extended in the line BC in XXI–XXV and clitellum from XIV–XXVII. Five new records are reported for the region, Dichogaster bolaui, Liodrilus mendesi, Pontoscolex (Pontoscolex) corethrurus, Urobenus brasiliensis and Urobenus petrerei.